KUALITAS SUSU SAPI SEGAR PADA PEMERAHAN PAGI DAN SORE - Nevia Wiranti; Veronica Wanniatie; Ali Husni; Arif Qisthon (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aims to determine the effect of milking time on the quality of fresh cow's milk. This research was carried out on June 2021, at Neang Mukti Ranch, Air Naningan District, Tanggamus Regency and at Mulia Farm Sukabanjar, Gedong Tataan District, Pesawaran Regency, Lampung. The research material used 7 liters of fresh cow's milk. The morning and evening milking data were obtained from the sum of the mean and standard deviation. The observed variables were alcohol, specific gravity, and reductase tests. This research was analyzed descriptively. The results showed that the morning and evening milking did not show any difference to the alcohol, specific gravity, and reductase tests.